Problematika Manajemen Pendidikan Agama Islam di Sekolah dan Kampus Umum - Mufarrihul Hazin; Alfi Laila (AKSI: Jurnal Manajemen Pendidikan Islam, 2022)
Islamic Religion education is the most important thing to implement in each education level from elementary, high school, and higher education, from basic formal public schools into campuses. The purpose of this study is to analyze the problems of Islamic religious education in public schools and campuses along with solutions to overcome them. The research method used in this research is library research using content analysis. The research results show that; First, the problems of Islamic religious education in public schools, namely the limited time allocation of only 2 hours of lessons per week, learning that is more oriented towards cognitive aspects, learning methods that are still traditional and boring, and the lack of competence of teachers. Second, the Problems of Islamic Religious Education on public campuses, namely: the provision of a very minimal credit load, only 2 credits, the provision of learning patterns that are less sustainable and only theoretical in nature, the form of developing an autonomous Islamic religious education, and Islamic religious lecturers who are not linear.